Effect of Firm Performance on Corporate Governance A Panel Data Analysis - Younas, Zahid Irshad; Mahmood, Haider; Saeed, Asif (Asian Journal of Empirical Research, 2013)
The purpose of this study is to investigate the impact of prior year firm’s performance on subsequent year firm’s corporate governance mechanism. We used board size, CEO–Chairman combined structure and audit expenditure as a firm level corporate governance mechanism. The panel data of fifty two companies listed on Karachi Stock Exchange covering the period from 2006 to 2010 was used for this study. Hypotheses were tested by using fixed effect model and random effect model. Our results revealed that prior year firm’s performance has positive relationship with board size but negative relationship with audit expenditure. Furthermore, any change in prior year firm’s performance causes change in CEO duality.